Forecasting hydraulic fracturing of low-permeability reservoir based on mathematical modeling and analysis of production data in the y field - Newfel M. Mahdi (Геология, горное и нефтегазовое дело (доклады на английском и немецком языках), 2021)
Заглавие с экрана